When a common complaint reveals an uncommon diagnosis – The Eagle syndrome - Fernandes, Dina Novais (2016)
Introduction: The Eagle syndrome is characterized by the elongation of styloid process. This provides attachment for many important neurovascular structures and can lead to a broad spectrum of symptoms. The most common symptoms include odynophagia and a sensation of a foreign body. It can also cause dysphagia, headache, syncope, or even transient ischemic attacks. The diagnosis is difficult as the symptoms may be attributed to other diseases. Case report: We describe the case of a 35-year-old female with persistent odynophagia for 8 months, with multiple consultations with her family doctor and the local emergency department. Physical examination revealed oropharyngeal erythema. Endoscopy and pharyngeal exudate were normal. The patient was referred to an otolaryngology consultation, but no cause was found. With persistent odynophagia and anxiety due to a lack of a diagnosis, computerized tomography of the pharynx was requested. This revealed asymmetry of the styloid process and the Eagle syndrome was diagnosed. Conservative management was suggested, but due to refractory symptoms, the patient was referred to stomatology. After consultation in hospital, the complaints of pain improved with anti-inflammatory therapy. The patient is currently followed in hospital with annual monitoring. Comment: Although the Eagle syndrome is rare, it should be considered in patients with chronic cervicofacial pain, especially when this is refractory to treatment. Otherwise, it may lead to incorrect diagnosis, to consumption of health resources, and to physical and emotional stress for the patient. The family doctor has a role to play in recognition this syndrome since the symptoms are commonly encountered in daily clinical practice.